Pengaruh Penyuntikan Dosis Ovaprim yang Berbeda Terhadap Waktu Ovulasi pada Ikan Mas Koki (Carassius auratus) - Ridho Febriansyah (PAKIS JOURNAL INSTITUTE, 2023)
Goldfish is one of the freshwater ornamental fish that is in great demand for the Indonesian community, but its production is still not meeting the demand of the market because it has to wait for the process of ovulation. Therefore, to accelerate the occurrence of the ovulation process can be done with the injection of the hormone ovaprim. So the purpose of this research is to determine the time of ovulation of the goldfish by doing the injection of the hormone ovaprim. The research was conducted for two months at the Djuanda Bogor University Fisheries Laboratory. The research design was a Complete Random Plan (RAL) with 4 treatments and 3 repetitions. Treatment K (control) did not give hormones, treatment A (0.3 mL/kg of female mother weight), treatment B (0.5 mL /kg of feminine mother body weight), C (0.7 ml / kg of femal mother weight) and 0.5 mL per kg of male mother for each treatment. Research shows the fastest.